If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + 7(3x + 4) = 0 Reorder the terms: 21 + 7(4 + 3x) = 0 21 + (4 * 7 + 3x * 7) = 0 21 + (28 + 21x) = 0 Combine like terms: 21 + 28 = 49 49 + 21x = 0 Solving 49 + 21x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 21x = 0 + -49 Combine like terms: 49 + -49 = 0 0 + 21x = 0 + -49 21x = 0 + -49 Combine like terms: 0 + -49 = -49 21x = -49 Divide each side by '21'. x = -2.333333333 Simplifying x = -2.333333333
| X^3-10x+25x=0 | | 12(x+11)=11 | | 5-n/2=10 | | 8-15=-7+8x | | a^3b^3+a^2b^2+ab= | | p^3+4p^2-9p-36=0 | | 4k=3k+4 | | f(8)=3x+6 | | 10x+8y=5000 | | (9x^3-4x^2+3x)-(7x^2+2x+6)= | | 2y-8/4=2 | | -18v+16v-7=9 | | 7y+2(y-3)=(y+1)-2 | | 6y+12x=13 | | 8x-6x=(-18) | | 34.60+5.5p=64.6+4.25p | | 2x-y=40 | | B-7.4=-.8 | | 3x+8x=-77 | | 10=6-2z | | x^3y+x^2y+x^2y^2= | | 2u+6-4(-3u-2)=2(u-1) | | x^2-6x+26=0 | | 2x+7y-2=0 | | -110=-4x-6x | | 7y+2(y+3)=(y+1)-2 | | 2+5(x+2)=22 | | 49+3x+5=90 | | 5xn=42 | | -3+x/7=2 | | 8-3x=-20 | | 2x-4(x-5)=-6+2x-2 |